Groundwater flow numerical analysis of the Sibillini Hydrostructure (Central Italy): system characterization and evaluation of hydrogeological changes after the Mw 6.5 Norcia Earthquake - Zullo, Enrica; Albano, Matteo; Saroli, Michele; Moro, Marco; Testa, Gabriel; Bonora, Nicola; Petitta, Marco; Reimann, Thomas; Doglioni, Carlo (Italian journal of engineering geology and environment, 2024)
The October 30th Norcia earthquake originated from the rupture of different segments of the Vettore-Bove normal fault system. The co-seismic rupture propagated up to the surface, causing important faulting and affecting the hydrodynamics of the Basal Aquifer of the Sibillini Mts. carbonate hydrostructure. Several long-lasting hydrogeological changes occurred at springs over the impacted area. Such changes indicate the disruption of the hydraulic sealing effect of the Vettore fault because of the co-seismic dislocation and the consequent groundwater flow increase through the broken fault. This work aims at characterizing the complex regional hydrogeologic system of the Sibillini Mts. and evaluating the important earthquake-induced hydrogeological changes by means of numerical modelling. A robust conceptual model has been defined according to tectonic and hydrogeological data and based on a 3D reconstruction of the Basal Aquifer. The regional-scale extent of the model allowed us the adoption of a simplified approach treating the carbonate aquifer as a continuous and homogeneous equivalent porous medium, while faults were considered as hydraulic barriers with lower permeability. Simulation results, aligned with the observed variations, highlight the crucial role of faults in influencing the hydrodynamics of carbonate hydrostructures.